2012
DOI: 10.1063/1.3681903
|View full text |Cite
|
Sign up to set email alerts
|

The Volleben effect in magnetic superconductors Dy1–xYxRh4B4 (x = 0.2, 0.3, 0.4, and 0.6)

Abstract: The Volleben effect (“paramagnetic” Meissner effect) was revealed for the first time while measuring the temperature dependence of magnetic moments of Dy1–xYxRh4B4 (x = 0.2, 0.3, 0.4, 0.6) in magnetic fields 1–20 Oe. The effect decreases with increasing magnetic field strength, and at fields below 1 Oe a diamagnetic signal appears. The ferromagnetism of Dy atoms supposedly plays an essential role in the appearance of paramagnetic signal at temperatures below the superconducting transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The observation of an anomalous paramagnetic magnetization signal (viz., paramagnetic Meissner effect (PME)), instead of the usual diamagnetic behaviour, on field-cooling a superconducting specimen, continues to attract [1,2] attention ever since its discovery [3] in ceramic sample(s) of a high T c cuprate. In addition to high T c cuprates [3][4][5][6][7][8][9][10][11][12], the PME-like attribute is known to occur in a wide variety of other superconductors [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Numerous explanations (see [27] for a review), e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of an anomalous paramagnetic magnetization signal (viz., paramagnetic Meissner effect (PME)), instead of the usual diamagnetic behaviour, on field-cooling a superconducting specimen, continues to attract [1,2] attention ever since its discovery [3] in ceramic sample(s) of a high T c cuprate. In addition to high T c cuprates [3][4][5][6][7][8][9][10][11][12], the PME-like attribute is known to occur in a wide variety of other superconductors [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Numerous explanations (see [27] for a review), e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to high T c cuprates [3][4][5][6][7][8][9][10][11][12], the PME-like attribute is known to occur in a wide variety of other superconductors [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Numerous explanations (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…6 We have recently detected the WE in Dy 1Àx Y x Rh 4 B 4 (x ¼ 0.2, 0.3, 0.4, and 0.6) superconductors. 12 These compounds have the feature that, with the appearance of superconductivity the magnetic ordering (ferromagnetism) does not vanish, but coexists with it down to the lowest experimentally attainable temperatures ($0.5 K). 13,14 We suggested that the internal magnetism of these compounds may play an important role in the development of the WE.…”
mentioning
confidence: 99%
“…Measurements of the specific heat of Dy 0.8 Y 0.2 Rh 4 B 4 (T M = 30.5 K, T c = 5.9 K) indicate emergence of another magnetic phase transition below 2.7 K [3]. Recently, anomalies of some physical quantities, unusual for systems with conventional superconductivity, were discovered in Dy 1−x Y x Rh 4 B 4 : the paramagnetic Meissner effect [4,5] and non-monotonic temperature dependencies of the upper critical magnetic field H c2 and the superconducting gap [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was found [2,3] that the magnetic ordering of Dy atoms may occur at the temperature T M higher than the superconducting transition temperature T c and coexist with superconductivity down to very low temperatures. It was established in [3] that Dy 1−x Y x Rh 4 B 4 belongs to materials with intrinsic ferrimagnetism, and the transition temperature T M strongly depends on the concentration of non-magnetic yttrium: it falls with increasing Y concentration from 37 K in DyRh 4 [2]. Measurements of the specific heat of Dy 0.8 Y 0.2 Rh 4 B 4 (T M = 30.5 K, T c = 5.9 K) indicate emergence of another magnetic phase transition below 2.7 K [3].…”
Section: Introductionmentioning
confidence: 99%